Pengembangan Permainan Domino Card Sebagai Upaya Pengenalan Huruf Anak Usia 5 – 6 Tahun - Meviayanti, Andhani; Ismiatun, Asih Nur; Hasni, Uswatul (Jurnal Ilmiah POTENSIA, 2025)
Letter recognition in children aged 5-6 years plays a crucial role in child development, particularly in language development, as it serves as the foundation for reading instruction. During this process, children learn to identify letter shapes, names, and sounds. A needs analysis conducted in four kindergartens in Jambi Luar Kota District revealed that children experience difficulties recognizing alphabet letters, and schools require innovative educational games to support letter recognition instruction. This research aims to: (1) develop a domino card game, (2) assess its feasibility, and (3) examine teachers' responses to the game. The study employed the ADDIE development model, which includes analysis, design, development, implementation, and evaluation phases. Data were collected through validation questionnaires completed by subject matter and media experts, and response questionnaires from six teachers at TK Negeri 15 Mendalo Darat and TK Labora Islam Mulia. Both quantitative and qualitative data analysis methods were used. Expert validation results showed high suitability scores: 98% from subject matter experts and 96% from media experts, indicating the domino card game requires no revision. Practicality testing by teachers yielded a score of 87%, demonstrating that the domino card game is practical and suitable as an educational tool for letter recognition among children aged 5-6 years in Jambi Luar Kota District. The development of innovative educational games is essential for providing varied learning experiences. However, this research is limited to field testing and has not yet conducted effectiveness testing.